Influence of Reaction Parameters on the Catalytic Upgrading of an Acetone, Butanol, and Ethanol (ABE) Mixture: Exploring New Routes for Modern Biorefineries - Ketabchi, Elham; Pastor-Pérez, Laura; Arellano-García, Harvey; Reina, Tomas Ramirez (Frontiers in Chemistry, 2020)
Here we present a comprehensive study on the effect of reaction parameters on the upgrade of an acetone, butanol and ethanol mixture – key molecules and platform products of great interest within the chemical sector. Using a selected high performing catalyst, Fe/MgO-Al2O3, the variation of temperature, reaction time, catalytic loading and reactant molar ratio have been examined in this reaction. This work is aiming to not only optimise the reaction conditions previously used, but to step towards using less energy, time and material by testing those conditions and analysing the sufficiency of the results. Herein we demonstrate that this reaction is favored at higher temperatures and longer reaction time. Also, we observe that increasing the catalyst loading had a positive effect on the product yields, while reactant ratios have shown to produce varied results due to the role of each reactant in the complex reaction network. In line with the aim of reducing energy and costs, this work showcases that the products from the upgrading route have significantly higher market value than the reactants, highlighting this process represents an appealing route to be implemented in modern biorefineries.